Manajemen Kurikulum di SDIT Mentari Ilmu Karawang - Mulyadi (Yayasan Sukma, 2024)
The curriculum is crucial to the success of the learning process, and curriculum management plays a vital role in achieving curriculum goals. This study aims to analyze curriculum management at IT Mentari Ilmu Elementary School in Karawang. This research focuses on curriculum management, which includes curriculum planning, organizing, implementation, and evaluation stages. A qualitative descriptive approach was adopted in this study. Data were collected through observations and interviews with the school principal, teachers, and curriculum developers' representatives. The data were analyzed using the methods of data reduction, data presentation, and drawing conclusions. The results indicate that curriculum management at IT Mentari Ilmu Elementary School has effectively followed the stages of planning, organizing, implementation, and evaluation.